PHYTOCHEMICAL AND ANTIMICROBIAL ACTIVITY OF THE LEAVES OF LANNEA KERSTINGII ENGL & K. KRAUSE (ANACADIACEAE) - NS, Njinga; MI, Sule; UU, Pateh; HS, Hassan; MM, Ahmad; ST, Abdullahi; BA, Danja; Bawa, B (Journal of Health and Allied Sciences NU, 2014)
The phytochemical and antimicrobial activity of the petroleum ether and crude methanol extracts, chloroform and ethyl acetate fractions of the leaves of Lannea kerstingii were investigated. Phytochemical screening revealed the presence of steroids and triterpenes in the petroleum ether extract, steroid, triterpene, flavonoids and tannins in both crude methanol extract and chloroform fraction while the ethyl acetate fraction contained only flavonoids and tannins. The extracts exhibited antimicrobial activities with zones of inhibition ranging from 17.00 to 21.03, 20.10 to 25.24, 25.32 to 34.02 and 22.28 to 27.20 mm for petroleum ether extract, methanol extract, chloroform and ethyl acetate fractions respectively. The minimum inhibitory concentration was between 5 and 10mg/ml, 5mg/ml for the petroleum ether and methanol extract respectively, and between 2.5 and 5 mg/ml, 5mg/ml for the acetate fractions. The minimum bactericidal concentration for all the extracts was 40mg/ml respectively except for chloroform fraction which ranged from 20 to 40mg/ml. The minimum fungicidal concentration for all the extracts was found to be 40mg/ml respectively. This result indicates the broad spectrum antimicrobial potential of L. Kerstingii and justifies the use of this plant in traditional medicine.
Keywords: antimicrobial; phytochemical; barteri; lannea kerstingii